Cognateosymtes serraticoxae, new genus, new species, a pleustid amphipod from the Sea of Japan (Crustacea: Amphipoda: Gammaridea: Pleustidae: Eosymtinae) - Labay, Vjacheslav S. (Zootaxa, 2018)
The new genus Cognateosymtes gen. nov. and new species C. serraticoxae sp. nov. are described from the shelf of western Sakhalin Island. The new genus has a set of features specific to the subfamily Eosymtinae: strongly ridged molar grinding surface of mandible and presence of a medial seta; inner plate of maxilla 1 with 2 strong apical plumose setae; inner plate of maxilla 2 with 2 strong submarginal setae, positioned subapically; pereopods 1 and 2 (gnathopods), propodal palmar margins lacking submedial tooth. Cognateosymtes differs from Eosymtes by the combination of character states: antenna 1, peduncular segment 1 with strong anterodistal processes; outer and inner plates of maxilla 2 with numerous apical setae; maxilliped, palp segment 2 linear, inner margin densely setose; coxae 1–3, posterodistal cusps multiple; dactylus of pereopods 3–7 the short. The key to the amphipod genera of the subfamily Eosymtinae Bousfield & Hendrycks, 1994 is given.